Registro de Thaumastocoris peregrinus (Hemiptera, Thaumastocoridae) no Estado do Paraná - Barbosa, Leonardo Rodrigues; Santos, Franciele; Wilcken, Carlos Frederico [UNESP]; Soliman, Everton P. [UNESP] (Embrapa Florestas, 2010)
It is recorded the occurrence of Thaumastocoris peregrinus Carpintero & Dellapé, 2006 (Hemiptera, Thaumastocoridae) in eucalyptus trees in the State of Parana, Brazil. The insect was observed in June at 2009, in Curitiba region.

É registrada a ocorrência de Thaumastocoris peregrinus Carpintero & Dellapé, 2006 (Hemiptera, Thaumastocoridae) em árvores de eucalipto no Estado do Paraná. Infestações foram observadas, em junho at 2009, na região de Curitiba.
Record of Thaumastocoris peregrinus (Hemiptera: Thaumastocoridae) in the State of Parana, Brazil
Keywords: Bronze Bug; Forestry pest; Eucalyptus; Percevejo bronzeado; Praga Florestal; Eucalyptus